Studi Komparatif Antara Mediasi di Peradilan Perdata dan Upaya Administratif di Peradilan Tata Usaha Negara - Amalia Wulandari; Chininta Ayu Candani Kriyandari; Nur Alfianah (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
In accordance with Article 25 paragraph (2) of the Law on Judicial Power, the general judiciary is one part of the judicial power that has the authority to examine, adjudicate, and issue decisions in criminal and civil cases in accordance with the applicable regulations. In civil trial proceedings at the district court, there are three stages: the preliminary stage, the determination stage, and the execution stage. In civil justice, there is an effort to resolve disputes outside of trial, namely mediation, and in administrative court proceedings, there is an effort to resolve disputes outside the court, namely administrative efforts. Mediation is an effort to resolve conflicts through deliberation with the assistance of a neutral third party, known as a mediator, to reach an agreement that can be accepted by both parties. This administrative effort is a resolution process carried out internally within an agency between the government and the party filing an objection to a state administrative decision before the dispute is brought to court. The purpose of this study is to understand the differences in non-litigation efforts between civil courts and state administrative courts. The research method is normative, using a statutory approach that emphasizes the analysis of regulations related to the main discussion of this study. In civil courts, mediation aims and focuses more on efficiency, which benefits both parties and, in turn, can reduce the burden on judges in resolving disputes in court. On the other hand, the purpose of administrative measures in state administrative cases is oriented towards internal government supervision, as a last resort, and rapid correction.